BMP growth factor signaling in a biomechanical context. (4th October 2013) - Kopf, Jessica; Paarmann, Pia; Hiepen, Christian; Horbelt, Daniel; Knaus, Petra
Abstract Bone Morphogenetic Proteins (BMPs) are members of the transforming growth factor‐β superfamily of secreted polypeptide growth factors and are important regulators in a multitude of cellular processes. To ensure the precise and balanced propagation of their pleiotropic signaling responses, BMPs and their corresponding signaling pathways are subject to tight control. A large variety of regulatory mechanisms throughout different biological levels combines into a complex network and provides the basis for physiological BMP function. This regulatory network not only includes biochemical factors but also mechanical cues. Both BMP signaling and mechanotransduction pathways are tightly interconnected and represent an elaborate signaling network active during development but also during organ homeostasis. Moreover, its dysregulation is associated with a number of human pathologies. A more detailed understanding of this crosstalk in respect to molecular interactions will be indispensable in the future, in particular to understand BMP‐related diseases as well as with regard to an efficient clinical application of BMP ligands. © 2013 BioFactors, 40(2):171–187, 2014